Tempe Flour Increase The Amount of Erythrocytes of White Male Rat (Rattus norvegicus) Wistar Strain Induced by Cigarette Smoke - I Made Subhawa Harsa (Faculty of Medicine, University of Jember, 2019)
Cigarette smoke was one of the free radical sources for the body. Free radical contain in cigarette smoke were hydroxide radicals (•OH). Hydroxide radicals would cause erythrocytes damage. Antioxidants were substances that can prevent free radicals. Now, natural antioxidants source has developed, one of that is tempe because it contains antioxidants substances such as carotene, Vitamin E, isoflavone, and factor II antioxidants. The aim of this study is knowing the influence of giving tempe flour toward the amount of erythrocytes of white male rat (Rattus norvegicus) Wistar strain induced by cigarette smoke. The experiment used a post-test only-control group design method. The samples were white male rats Wistar strain aged of 3 to 4 months as much 30 rats with weight around 180-220 gram. The samples divided into three groups, that were control group (K1), treatment group 1 (K2), and treatment group 2 (K3), each group consists of 10 rats. Control group was not given any treatment, it only got a standard feed, treatment group 1 got treatment and it was induced by cigarette smoke. Furthermore, treatment group 2 got standard feed, it was induced by cigarette smoke and was given tempe. Analysis of data used one-way anova showed the significance p-value = 0,036 that was <α (0,05). The result showed giving tempe flour increase the amounts of erythrocytes of white male rat (Rattus norvegicus) Wistar strain which was induced by cigarette smoke. Keywords: cigarette smoke, free radicals, erythrocytes, antioxidants, tempe